m6A Reader HNRNPA2B1 Promotes Esophageal Cancer Progression via Up-Regulation of ACLY and ACC1 - Guo, Huimin; Wang, Bei; Xu, Kaiyue; Nie, Ling; Fu, Yao; Wang, Zhangding; Wang, Qiang; Wang, Shouyu; Zou, Xiaoping (Frontiers in Oncology, 2020)
N6-methyladenosine (m6A) modification is the most abundant modification on eukaryotic RNA. In recent years, lots of studies have reported that m6A modification and m6A RNA methylation regulators were involved in cancer progression. However, the m6A level and its regulators in esophageal cancer (ESCA) remain poorly understood. In this study, we analyzed the expression of m6A regulators using The Cancer Genome Atlas (TCGA) data, and found 14 of 19 m6A regulators are significantly increased in ESCA samples. Then we performed a univariate Cox regression analysis and LASSO Cox regression model to investigate the prognostic role of m6A regulators in ESCA, and the results indicated that a two-gene prognostic signature including ALKBH5 and HNRNPA2B1 could predict overall survival (OS) of ESCA patients. Moreover, HNRNPA2B1 is higher expressed in high risk scores subtype of ESCA, indicating that HNRNPA2B1 may be involved in ESCA development. Subsequently, we confirmed that the level of m6A and HNRNPA2B1 was significantly increased in ESCA. We also found that HNRNPA2B1 expression positively correlated with tumor diameter and lymphatic metastasis of ESCA. Moreover, functional study showed that knockdown of HNRNPA2B1 inhibited the proliferation, migration and invasion of ESCA. Mechanistically, we found that knockdown of HNRNPA2B1 inhibited the expression of de novo fatty acid synthetic enzymes, ACLY and ACC1, and subsequently suppressed cellular lipid accumulation. In conclusion, our study provides critical clues to understand the role of m6A and its regulators in ESCA. Moreover, HNRNPA2B1 functions as an oncogenic factor in promoting ESCA progression via up-regulation of fatty acid synthesis enzymes ACLY and ACC1, and it may be a promising prognostic biomarker and therapeutic target for human ESCA.